Dancing on the edge [videorecording (DVD)] - Poliakoff, Stephen, 1952-; Ejiofor, Chiwetel, 1977-; Goode, Matthew, 1978-; Bisset, Jacqueline, 1944-; Hughes, Tom, 1986-; Goodman, John, 1952- (PBS, 2015)
A PBS miniseries in which a black jazz band becomes a huge success and ends up entangled in the aristocratic world of 1930s London as they seek fame and fortune.